Markets - Beverungen, Armin; Mirowski, Philip; Nik-Khah, Edward (In Search of Media, 2019)
Markets abound in media-but a media theory of markets is still emerging. Anthropology offers media archaeologies of markets, and the sociology of markets and finance unravels how contemporary financial markets have witnessed a media technological arms race. Building on such work, this volume brings together key thinkers of economic studies with German media theory, describes the central role of the media specificity of markets in new detail and inflects them in three distinct ways. Nik-Khah and Mirowski show how the denigration of human cognition and the concomitant faith in computation prevalent in contemporary market-design practices rely on neoliberal conceptions of information in markets. Schröter confronts the asymmetries and abstractions that characterize money as a medium and explores the absence of money in media. Beverungen situates these inflections and gathers further elements for a politically and historically attuned media theory of markets concerned with contemporary phenomena such as high-frequency trading and cryptocurrencies.